Gugatan Pembatalan Merek Sebagai Upaya Hukum Memerangi Fenomena Trademark Bullying yang didasari oleh Penggunaan Merek dengan Kata Umum - Suwandi, Dinda Amelia (Media Hukum Indonesia (MHI), 2025)
The phenomenon of trademark bullying occurs when trademark owners excessively exercise their rights to pressure other parties, particularly in cases involving marks that use common words or lack distinctiveness. Weak distinctiveness parameters in the first-to-file system allow generic marks to remain registered and potentially be misused, as seen in the Campus/Kampus vs. Distinction case. This normative juridical research shows that the use of common words in trademarks is a primary trigger of intimidation, as trademark owners can claim a monopoly over terms that should be freely available for public use. Decision Number 25 K/Pdt.Sus-HKI/2014, which annulled the “Campus/Kampus” trademark, demonstrates that trademark cancellation lawsuits are an effective means to counter trademark bullying. These findings highlight the need to tighten substantive examination, enforce the principle of good faith, and strengthen restrictions on the use of common terms in trademark registration.